Characterization of 45 cases of congenital lung malformation and association of inflammation with symptomatology - Susanna Nuutinen; Elisa Lappi-Blanco; Eveliina Ronkainen; Teija Dunder; Terttu Harju; Willy Serlo; Jaakko Sinikumpu (Scientific Reports)
Abstract Lung development begins during week 4 of pregnancy and continues through fetal development until early infancy. Various malformations can develop during the fetal period. There is histology overlap in several of them and partly joint etiology has been suggested as the cause of malformation. Early surgery has been supported after the diagnosis of a local pulmonary malformation due to potential malignancy risk and an increased lung infection risk. However, the evidence supporting surgery for asymptomatic patients is scarce. This comprehensive single-center study in a tertiary children’s hospital included all 45 surgically treated patients at any age between 1986 and 2015. The study population consisted of 45 patients. Histology, preoperative symptoms, and radiological and operative findings were systematically reevaluated. Small cyst type congenital pulmonary airway malformation (CPAM) was the most common type of detected congenital lung malformation. There were no malignant or premalignant findings. Of all the patients, 23 (48.9%) were asymptomatic at the time of surgery. However, histology showed that four out of them (18%) had ongoing inflammation. Overall, one third of patients (n = 15, 34%) presented to have inflammation histologically. While chronic inflammation results in alveolar fibrosis, a high reported inflammation rate (34%) supports early malformation excision, regardless of the symptoms.